Comparative analysis of aldehyde dehydrogenase 1 expression in polyps and adenocarcinoma of the distal colon - Shyshkin, M. A.; Khrystenko, T. O.; Шишкін, Максим Андрійович; Христенко, Тетяна Олексіївна (My University, 2020)
Aldehyde dehydrogenase 1 (ALDH1) is one of the most widely used cancer stem cells markers, even though the question of its significance for certain stages of colorectal carcinogenesis is still unclear. The aim of this study was to compare ALDH1 immunohistochemical expression levels in polyps and adenocarcinoma of the distal colon. Histopathological and immunohistochemical studies of biopsies from 40 patients (biopsies of polyps and histologically non-changed mucosa of the distal colon), as well as surgical material of colorectal adenocarcinoma from 30 patients were carried out. It was established that distal colonic polyps are characterized by cytoplasmic expression of ALDH1 with the median of relative area that is equal to 25.63 (18.26; 30.42)% stromal cells. ALDH1 expression by epitheliocytes is revealed exclusively in dysplastic polyps with the median of the area that is equal to 22.13 (17.22; 30.05)%. Colorectal adenocarcinoma is characterized by cytoplasmic expression of ALDH1 with the medians of the area that are equal to 40,22 (22,54; 47,77)% stromal cells and 32,12 (23.64; 40.28)% cancer cells. The area of ALDH1+ cells varies depending on the pTNM stage of the carcinoma, herewith the median of ALDH1+ stromal cells is significantly increasing during the tumor progression from the I to the III stages that displays increasing in number of stromal cells which are involved in oncogenic signaling pathways activation. The median of ALDH1+ cancer cells is significantly increasing during the tumor progression from the III to the IV stages that shows increasing number of cancer cells that acquire properties of stem cells on advanced stages of colorectal adenocarcinoma. Comparative analysis of the parameters obtained for polyps and carcinoma indicates that the median of ALDH1+ stromal cells area in polyps is 2 times smaller than the median of ALDH1+ stromal cells area in carcinoma, and the median of ALDH1+ epitheliocytes area in polyps is 1.5 times smaller than the median of ALDH1+ cancer cells area.

Альдегіддегідрогеназа 1 (ALDH1) є одним з найчастіше використовуваних маркерів ракових стовбурових клітин, проте питання щодо його значущості відносно окремих етапів колоректального канцерогенезу лишається до кінця не вивченим. Метою цього дослідження стало порівняння рівнів імуногістохімічної експресії ALDH1 в поліпах і аденокарциномі дистальної товстої кишки. Проведено патоморфологічне та імуногістохімічне дослідження біопсійного матеріалу 40 пацієнтів (біоптати поліпів і гістологічно незміненої слизової оболонки дистальної товстої кишки), а також операційного матеріалу колоректальної аденокарциноми 30 пацієнтів. Установлено, що поліпи дистальної товстої кишки характеризуються цитоплазматичною експресією ALDH1 з медіаною відносної площі 25,63 (18,26; 30,42)% клітин строми, а також, що експресія маркера епітеліоцитами виявляється виключно в диспластично змінених поліпах з медіаною площі 22,13 (17,22; 30,05)%. Колоректальна аденокарцинома характеризується цитоплазматичною експресією ALDH1 з медіанами площі 40,22 (22,54; 47,77)% клітин строми та 32,12 (23,64; 40,28)% ракових клітин. Показник площі ALDH1+ клітин варіює залежно від стадії карциноми за pTNM, при цьому медіана площі ALDH1+ клітин строми достовірно збільшується при прогресії пухлини від I до III стадії, що відображає збільшення кількості клітин строми, залучених до активації туморогенних сигнальних шляхів. Медіана площі ALDH1+ ракових клітин достовірно збільшується при прогресії пухлини від III до IV стадії, що відображає збільшення кількості ракових клітин, що набувають властивостей стовбурових, на просунутих стадіях колоректальної аденокарциноми. Порівняльний аналіз показників, отриманих для поліпів і карциноми, вказує на те, що медіана площі ALDH1+ клітин строми поліпів в 2 рази менша за медіану площі ALDH1+ клітин строми карциноми, а медіана площі ALDH1+ епітеліоцитів поліпів в 1,5 раза менша за медіану площі ALDH1+ ракових клітин.
Порівняльний аналіз експресії альдегіддегідрогенази 1 в поліпах і аденокарциномі дистальної товстої кишки.
Keywords: polyps; olorectal cancer; aldehyde dehydrogenase 1; поліпи; колоректальний рак; альдегіддегідрогеназа 1